Computerised tomography after recent severe head injury in patients without acute intracranial haematoma. Issue 3 (March 1979) - Snoek, J; Jennett, B; Adams, J H; Graham, D I; Doyle, D
Abstract : Sixty patients with severe head injury who did not have an acute intracranial haematoma on CAT scanning are reviewed. The scans are correlated with the level of consciousness at the time of scanning and with the outcome six months after injury. The initial scan was interpreted as being normal in 38% of the cases. In the remainder the most common abnormalities were small ventricles and areas of mixed increased and decreased density interpreted as contusions. All the patients with small ventricles were under 20 years of age. Postmortem examinations were undertaken on 15 of the 19 fatal cases. There was evidence of a high intracranial pressure in 12, cerebral contusions were absent or minimal in 10, there was diffuse immediate impact damage to white matter in six, and there was moderate or severe hypoxic damage in four.